IMPLEMENTASI SUPERVISI AKADEMIK PENGAWAS DI SMP - Khaerul, Khaerul (Eklektika: Jurnal Pemikiran dan Penelitian Administrasi Pendidikan, 2014)
The study aimed at discovering (i) the description of teh implementation of academic supervision of supervisor at SMPN Katumbangan Lemo in Polewali Mandar district, (ii) the factors which influence academic supervision of supervisor at SMPN Katumbangan Lemo in Polewali Mandar district. The study is aqualitative research with a case study approach. The study provided in-depth description on the implementation of academic supervision of supervisor at SMPN Katumbangan Lemo in Polewali Mandar district. Data sources were taken purposively. Data were collected through interview, obervation, and documentation then validated through triangulation and meber check. The results of the study revealed that (i) the implementation of academic supervision of supervisor at SMPN Katumbangan Lemo in Polewali Mandar district ran well by applying supervision principles: scientific principle, democratic principle, constructive and creative principles, and partnership principle; by applying supervision techniques: individual technique such as class visit, class observation, and teaching demonstration, and group techniques such as teacher meeting, group study of teachers and MGMP, and discussion as a group process which applied supervision mode: scientific model, artistic model, and clinical model; the factors which influenced academic supervision of supervisor were the internal and external factors. The internal factors were strong commitment of supervisor, academic competence of supervisor in terms of ability in guiding to arrange the syllabus, lesson plan, the selection and use of method, the use of media and learning facility, the utilization of information technology, guiding to teach in class, and guiding and evaluating the process of teaching, and highly motivation of supervisor. Whereas, the external factors of supervisor were empowerment of supervisor by the superior by giving the authority, good working environment, friendly, conducive, pleasant, working together and supported each other, and the superior policy factor towards supervisor in providing support and decision making from Kadisdikpora and the principal based on the recommendation from the supervisor in terms of the improvement of teaching quality in school.